Analysis of Resistivity Value Distribution for Identification of Aquifer Layers in South Palangga District, South Konawe - Aqsal Ramdhan Shaddad; La Ode Dzakir (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2026)
This study aims to analyze the distribution of subsurface resistivity values ​​to identify aquifer layers in South Palangga District, South Konawe Regency. The method used was geoelectric resistivity with a Wenner–Schlumberger configuration. Data acquisition was carried out on three lines, each 200 meters long and with electrode spacing of 10 meters. The measured data, in the form of apparent resistivity, were then processed using RES2DINV software to generate a two-dimensional (2D) subsurface cross-section model. The results showed that resistivity values ​​in the study area ranged from 1.61 to 43,164 Ωm, with a penetration depth of 40–55 meters. Interpretation of the resistivity cross-section indicated the presence of two main zones: a conductive zone and a resistive zone. The conductive zone, with resistivity values ​​of 1.61–76.4 Ωm, is interpreted as a water-saturated weathering layer and functions as a shallow aquifer with a thickness of approximately 20 meters. Meanwhile, resistive zones with resistivity values ​​greater than 76.4 Ωm are interpreted as relatively compact limestone bedrock. A comparative analysis between the two tracks indicates that track 2 has the most prospective aquifer potential, characterized by lower resistivity values ​​and a wider lateral distribution. Overall, the resistivity geoelectric method has proven effective in identifying the distribution of shallow aquifers and the characteristics of subsurface lithology. The results of this study are expected to provide a basis for planning the exploration and utilization of groundwater resources in the study area.